The impact of an HIV/AIDS workplace wellness programme in a large packaging factory - Janse van Rensburg, Michelle Nedine Schorn (My University, 2008)
ABSTRACT Introduction: As the impact of HIV/AIDS on the business sector has become more visible, businesses have increasingly seen the advantages of creating HIV/AIDS management programmes for their workplaces – and some even beyond the workplace, to their surrounding communities. The aim of the study was to determine the effect and benefit of a large company’s HIV/AIDS workplace wellness programme. Study objectives were to a) describe the effect of the wellness programme as measured by differences in CD4 counts and percentages, weight, episodes of diarrhoea and sick leave; and b) to explore the perceptions and views of the occupational health nursing practitioners (OHNPs) regarding what they observe the benefit of the wellness programme to be on the general sense of health and well-being of the HIV-positive employees. Materials and methods: The study was performed at 10 of the Gauteng factories of a large multi-national packaging company. Quantitative data was collected by means of a confidential retrospective review of 36 HIV-positive employees’ occupational health records. Mostly descriptive and some inferential data analysis was performed. Qualitative measurement was done through semi-structured interviews with nine OHNPs to gain information about their perceptions and opinions regarding the benefit of the wellness programme. Thematic analysis of qualitative data was carried out. Results: The benefit of the HIV workplace wellness programme was not seen when considering CD4 counts and CD4 percentages. Episodes of diarrhoea over time and absenteeism data also did not show any benefit. However, changes in weight were observed (participants gained an average of 1.5kg over the study period) although this was not statistically significant. The qualitative data showed that employees benefit from the wellness programme, particularly in terms of their physical and mental well-being. Emerging themes related to fear of loosing one’s job and denial of the reality of HIV/AIDS; stigma and discrimination in the workplace and in the community at large; trust versus mistrust of the Company’s HIV management system; acceptance of the condition; the acceptability of nutritional supplements; and the general benefit of the wellness programme. Other related themes that emerged included issues regarding VCT, peer education, the provision of anti-retroviral therapy (ART), the role of trade unions, barriers in the public health care system and OHNPs’ frustrations with the wellness programme. Discussion: The most beneficial aspect of the wellness programme appeared to be the trust relationship that employees on the wellness programme have with the OHNPs. Because of this, employees experience a sense of support and are more likely to accept their HIV-positive condition. This contributes to a sense of mental well-being. Early intervention and better management of the condition also occur and there is better compliance to treatment and disease management protocols. There was also a general sentiment that there were benefits in the use of nutritional supplements. Employees reported feeling healthier (e.g. having more energy when using nutritional supplements) and this contributed to a sense of physical well-being. A big challenge is to overcome mistrust amongst the general employee population who have not joined the wellness programme and to deal with the ever-present issues relating to the fear of loosing their job if found to be HIV-positive as well as denial of the condition. This fear and denial perpetuates the reality of discrimination and stigmatisation, which inevitably negatively affects the social well-being of HIV-positive employees. Limitations of the study included a small sample size; inconsistent data collection methods by the OHNPs in the various clinics; the complicated nature of nutritional supplementation, which makes it difficult to study superficially; and that HIV-positive employees could not be interviewed directly as they were not willing to be interviewed. Recommendations: Further research should be performed in the area of workplace wellness programmes. More efficient data collection systems should be put in place to measure the impact of HIV/AIDS and the effectiveness of workplace interventions. HIV-positive employees who have disclosed their status could be used as positive role models in HIV/AIDS programmes. Confidentiality protocols should continue to be strictly adhered to as this promotes the trust relationship. An HIV/AIDS nutritional expert should be involved in advising about the use of optimal supplements in the wellness programmes as OHNPs have differing opinions. Other health professionals could be involved in HIV wellness programmes, e.g. occupational therapists, social workers, etc. Companies should investigate how they can get involved in HIV/AIDS-related activities and partnerships in the communities where their employees live as many employees struggle with issues of poverty over-and-above being HIV-positive.
Keywords: HIV/AIDS; workplace wellness programme